2006
DOI: 10.1079/asc20053
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of oat hulls in diets for young pigs based on cooked maize or cooked rice

Abstract: An experiment was conducted to investigate the influence of the main cereal (cooked maize or cooked rice) and the inclusion of cooked and expanded oat hulls (0, 20 or 40 g/kg) in the diet on total tract apparent nutrient digestibility (TTAD) and productive performance of piglets weaned at 21 days. Each of the six treatments was replicated eight times (five piglets penned together) and the trial lasted for 33 days. From 21 to 41 days of age piglets were given their respective experimental complex diets that con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
110
2
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(129 citation statements)
references
References 22 publications
11
110
2
6
Order By: Relevance
“…Although Mateos et al (2006) have recommended that the diets of piglets weighing between 6 and 12 kg contain 60 g NDF per kg, it was observed in the present study that diets with about 110 g NDF per kg did not reduce the performance of piglets.…”
Section: Resultscontrasting
confidence: 83%
“…Although Mateos et al (2006) have recommended that the diets of piglets weighing between 6 and 12 kg contain 60 g NDF per kg, it was observed in the present study that diets with about 110 g NDF per kg did not reduce the performance of piglets.…”
Section: Resultscontrasting
confidence: 83%
“…v.72, n.5, p.400-410, September/October 2015 piglets receiving the control diet and the diet containing purified cellulose in relation to the piglets fed with the diet containing soybean hulls as the main source of fiber. The lower occurrence of E. coli in the small intestine of piglets fed diets containing soybean hulls and citrus pulp can be related to the higher quantity of soluble fiber present in these two ingredients, which increase fermentation and consequently, the production of short chain fatty acids, which inhibit the growth of this bacterium (Mateos et al, 2006). Similarly, Schiavon et al (2004) verified a reduction in the quantity of E. coli in the feces of piglets fed with 12 % beet pulp in the diet.…”
Section: Sci Agric V72 N5 P400-410 September/october 2015mentioning
confidence: 82%
“…Han et al, (2005) and Hanczakoswska et al, (2008) observed improvements in productive parameters and parameters related to the intestinal health of the animals. These differences in results are related to the type and quantity of fiber added to the diets (Mateos et al, 2006;Molist et al, 2009). Högberg and Lindberg (2004) suggest that positive effects in weight gain when the animals received sources of fiber in the diets can be related to the increase in size of the digestive organs.…”
Section: Assaymentioning
confidence: 99%
“…Values correspond to actual feed intake (feed disappearance minus feed wastage). Percentage of days in which piglets had symptoms of diarrhoea with respect to total number of days in experiment (Mateos et al, 2006). higher DM digestibility of diets based on HP-SBM than in isonutritive diets based on R-SBM.…”
Section: Discussionmentioning
confidence: 96%
“…Average daily gain (ADG), actual ADFI (calculated by difference between feed offered and feed wastage by pen) and FGR were calculated from these data by phase and for the entire experimental period. Post weaning diarrhoea (PWD) was estimated by pen as the proportion of days in which pigs showed clinical signs of diarrhoea with respect to the total number of days on trial (Mateos et al, 2006).…”
Section: Methodsmentioning
confidence: 99%